Clinicopathological study of cutaneous adnexal cyst with some unusual presentation - Singh, Praneeta Jaswant; Dahiya , Himani (Journal of Pathology of Nepal, 2021)
Background: Cutaneous cysts are slow-growing benign intradermal or subcutaneous tumors that occur commonly in the hair-bearing areas of the body. Sometimes they occur in non-hair-bearing areas due to traumatic implantation of the epidermis. The present study was conducted to determine the prevalence of various cutaneous cysts in our hospital set up, to record an unusual presentation and clinico-histopathological correlation. Material and methods: This is a hospital-based retrospective analysis of cutaneous cysts conducted for 6 months. All skin biopsies diagnosed under the category of the cutaneous cyst were included in the study. Histopathology slides stained with Hematoxylin and eosin were analyzed. Results: A total of 185 cases of cutaneous cysts were included in the study. The most frequent cutaneous cyst was an epidermal cyst (75.13%) followed by a dermoid cyst (18.38%). Epidermal cysts occurred at unusual locations of the palm, lower extremity, and breast. Unusual locations of the dermoid cyst were the floor of the mouth, gluteal region, scalp, and back. Two cases of scrotal epidermal cysts were associated with idiopathic calcinosis of the scrotum. In one case each proliferating trichilemmal cyst and apocrine hidrocystoma occurred over the unusual location of the back while cysticercosis occurred at an unusual location of the scalp. Inflammatory changes were found in 27 cases (14.59%) of cutaneous cysts. An overall clinicopathological correlation was seen in 91.89% (170/185) cases of cutaneous cysts Conclusions: Unusual clinical presentation of cutaneous cysts can pose a diagnostic dilemma. Definitive diagnosis in such cases is possible by histopathological analysis.